Serviço social e cultura: processos criativos na mediação do trabalho profissional - Santos, Juliana Abramides dos (2014)
The particular object of this study is the mediation of creative processes in professional work from the observation and analysis of the everyday three 'quilombos' communities: Matias, Maú and Juaba inside of Pará and the population of the slums Irati and Trianon, in Taboão da Serra municipality, in the state of São Paulo. This study sought to understand, systematize and analyze the creative processes, taking into account professional experience and activities undertaken by the social worker in quilombolas villages and slums. The creative process articulated to ontological - theoretical perspective developed in two dimensions: the recognition of cultural expressions of the residents of slums and quilombos and interdisciplinary professional practice creative and innovative. Social work when dealing with cultural expressions and creative experiences can contribute to new forms of professional intervention. This perspective is anchored to the professional project of the Brazilian Social Service break with conservatism articulated to the corporate project of human emancipation